Hepatitis E virus infection in a patient with alcohol related chronic liver disease: a case report of acute-on-chronic liver failure - Fantilli, Anabella Clara (2021)
Background: The hepatitis E virus (HEV) infection has been described as a causing factor for acute-on-chronic-liverfailure (ACLF) in patients with underlying chronic liver disease (CLD), such as chronic hepatitis or cirrhosis, which could end in the failure of one or more organs and high short-term mortality. There are scarce data about the association of HEV in patients with chronic liver disorders in South America. Case presentation: A 56-year-old hypertensive male with a history of type 2 diabetes was diagnosed with alcoholrelated-liver cirrhosis in February 2019. A year later, the patient was admitted to hospital due to fatigue, jaundice and acholia. No evidence of hepatitis A virus, hepatitis B virus, hepatitis C virus, Epstein–Barr virus, herpes zoster virus and cytomegalovirus infections were found. Nevertheless, in February and March, 2020 the patient was positive for HEVIgM and HEV-IgG, and HEV genotype 3 RNA was detected in sera. Afterwards, he presented grade I hepatic encephalopathy and, therefore, was diagnosed with acute hepatitis E-on-chronic liver disease. The patient reported a recent travel to the Argentine coast, where he consumed seafood. Besides, he reveled to have consumed pork meat and had no history of blood transfusion. Conclusion: This report describes a unique case of hepatitis E virus infection in a patient with alcohol-related cirrhosis. This is the frst report of a patient with HEV-related ACLF in Argentina and it invokes the importance of HEV surveillance and treatment among patients with CLD, such as alcohol-related cirrhosis.